The Analysis of Translation Techniques in Translating Fairytale Story “The Adventure of Pinocchio” (English-Indonesian Version) - Nurullah Hairunnisa Latingara; Novriyanto Napu; Jefriyanto Saud (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2023)
This research aims to analyze the translation techniques employed in the English-Indonesian translation of Carlo Collodi's "The Adventure of Pinocchio." By utilizing Molina and Albir's translation techniques, the study explores the specific methods used by the translator, Lulu Wijaya. The objective of this research is to gain insights into the translation techniques utilized in fairy tales and their implications for cross-cultural communication and children's literature. Using a qualitative approach, data were collected through the analysis of documents. The researcher identified 312 instances of translation techniques, which were categorized into nine types. These included adaptation (62 cases), compensation (71 cases), borrowing (1 case), amplification (3 cases), discursive creation (4 cases), established equivalent (1 case), literal translation (150 cases), modulation (6 cases), and reduction (14 cases). Notably, the most prevalent technique employed by Lulu Wijaya was literal translation. The findings of this research shed light on the prevalent use of literal translation in the translation of fairy tales, specifically "The Adventure of Pinocchio." Understanding these translation techniques is valuable for the field of translation studies, providing insights into the challenges and considerations involved in translating children's literature. Furthermore, these findings have implications for cross-cultural communication and the effective conveyance of meaning to young readers. This research contributes to the understanding of translation techniques in fairy tales, emphasizing their significance and potential applications in the broader context of literature and intercultural exchange.